2011
DOI: 10.1007/s00531-011-0671-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate diagenesis and feldspar alteration in fracture-related bleaching zones (Buntsandstein, central Germany): possible link to CO2-influenced fluid–mineral reactions

Abstract: Fracture-related bleaching of Lower Triassic Buntsandstein red beds of central Germany was related to significant carbonate diagenesis and feldspar alteration caused by CO 2 -rich fluids. Using cathodoluminescence microscopy and spectroscopy combined with electron microprobe analysis and stable carbon isotope study, two major fluid-mineral interactions were detected: (1) zoned, joint-filling calcites and zoned pore-filling calcite cements, the latter replacing an earlier dolomite, were formed during bleaching.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Another explanation for the 580 nm emission is a possible structural defect (strong local disorder) as it was reported from altered feldspar crystals (Gonz alez-Acebr on et al 2012; Wendler et al 2012). In these altered feldspars a structural disorder led to a local amorphization and produces an emission band at around 590 nm.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Another explanation for the 580 nm emission is a possible structural defect (strong local disorder) as it was reported from altered feldspar crystals (Gonz alez-Acebr on et al 2012; Wendler et al 2012). In these altered feldspars a structural disorder led to a local amorphization and produces an emission band at around 590 nm.…”
Section: Resultsmentioning
confidence: 82%
“…; Wendler et al. ). In these altered feldspars a structural disorder led to a local amorphization and produces an emission band at around 590 nm.…”
Section: Resultsmentioning
confidence: 98%
“…Other studies have described ''bleaching'' of red beds likely caused by migration of oil, methane, reducing brines, or CO 2 -charged brine (e.g., Beitler et al 2005;Loope et al 2010;Wendler et al 2012;Wigley et al 2012). Whitening associated with hydrocarbon migration and seeps is well documented in numerous previous studies (see compilation in Petrovic et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Conversely, closed system diagenesis in sandstones is assumed by many of those who study silicate diagenesis and sandstone reservoir quality of (Lander & Walderhaug ) although recent studies have suggested that material flux via fault systems may be a significant aspect of sandstone diagenesis in some circumstances (Wendler et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Now of interest as natural analogues to CO 2 geological sites, it is evident that movement of large quantities of CO 2 is a normal aspect of basin evolution (Baines & Worden 2004). Conversely, closed system diagenesis in sandstones is assumed by many of those who study silicate diagenesis and sandstone reservoir quality of (Lander & Walderhaug 1999) although recent studies have suggested that material flux via fault systems may be a significant aspect of sandstone diagenesis in some circumstances (Wendler et al 2012).…”
Section: Introductionmentioning
confidence: 99%